Strategi Pengembangan Kelompok Pengrajin Pandan Wangi di Desa Tumbu, Kecamatan Karangasem, Kabupaten Karangasem, Provinsi Bali - LESTARIANI, PUTU ASRI CIPTA; PARINING, NYOMAN; DIARTA, I KETUT SURYA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Pandan Wangi Craftsmen Group Development Strategy in Tumbu Village, Karangasem District, Karangasem Regency, Bali Province Tumbu Village is located in Karangasem District, Karangasem Regency, Bali Province with an area of approximately 400 Ha, with a residential area in its center. Tumbu Village has abundant potential and wealth with a series of hills, rice fields, gardens. The village borders the sea, overlooking the southern Lombok Strait. Tumbu Village is the center of pandanus mat craftsmen in Karangasem Regency. The purpose of this study is to determine internal and external factors and strategies of the Pandan Wangi Craftsmen Group development process in Tumbu Village, Karangasem District, Karangasem Regency. The results show that the internal factor that became a force in the Pandan Wangi Craftsmen Group Development is to have raw materials that are available continuously. An internal factor which is a weakness in the development of the Pandan Wangi Craftsmen Group is the relatively small number of members. While the external factor that became an opportunity in the development of the Pandan Wangi Craftsmen Group that Tumbu Village which has a tourist attraction in Soekasada Ujung Park and the challenge is that raw materials decline during the prolonged dry season and prices soar up. The Pandan Wangi Craftsmen Group Development Strategy is obtained from the results of the SWOT Matrix.